2013
DOI: 10.1080/17461391.2013.777797
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ankle dorsiflexion on jumping capacity and the modified agilityt-test performance

Abstract: Dorsiflexion sport shoes aim to increase jumping capacity and speed by means of a lower position of the heel in comparison with the forefoot, favouring additional stretching of the ankle plantar flexors. In previous studies, contradictory results have been found on the benefits of using this type of shoe. With the aim of comparing a dorsiflexion sport shoe model (DF) with a conventional sport shoe (CS), 41 participants performed a countermovement jump (CMJ) test and an agility test (MAT) with both models of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Acceleration and movement velocity were measured in this study using the t-test (27). The agility t-test required players to move through a T-shaped circuit to simulate the fast movements used in volleyball digs, receptions, and blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration and movement velocity were measured in this study using the t-test (27). The agility t-test required players to move through a T-shaped circuit to simulate the fast movements used in volleyball digs, receptions, and blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the larger ankle variation range of ev-inversion and int-external rotation of HSM conformed to kinetic results that peak pressure of HSM tended to shift laterally compared with HBM. Moreover, Salinero et al stated that although increased ankle dorsiflexion could affect muscle activation, it would not improve jump performance (Salinero et al 2014). This is consistent with the result in this study that HBM and HSM showed comparable jump height with different ankle position in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…While the forefoot generates force by pushing against the ground to provide propulsion during take-off, increase of toe flexor strength (as reflected by higher MTPJ stiffness) leads to better long jump performance (Goldman et al 2013; Man et al, 2016b;Morita et al, 2015). Increased MTPJ stiffness may tighten the foot intrinsic muscles ligament and plantar fascia and thus increase leg stiffness (Frank et al, 2000;Larkins & Snabb, 1999;Salinero et al, 2014). Larger leg stiffness is associated with better take-off velocity and jump height (Struzik & Zawadzki, 2013), as indicated by the higher GRF generated.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies did not examine changes in forefoot biomechanics and MTPJ stiffness that denotes the mechanical characteristics of the forefoot. This may influence the muscle mechanics of the intrinsic foot muscle as well as proximal joint stiffness (Frank et al, 2000;Larkins & Snabb, 1999;Salinero et al, 2014). In relation to the fact that no energy is generated at MTPJ during take-off (Stefanyshyn et al, 2016), the differences in forefoot rolling mechanics (angle, velocity and loading) among static, consecutive and running jumps could result in distinct adaption of the individual MTPJ.…”
Section: Introductionmentioning
confidence: 99%